Postural response of intraocular pressure in chronic open-angle glaucoma following trabeculectomy. Issue 7 (July 1987) - Parsley, J; Powell, R G; Keightley, S J; Elkington, A R
Abstract : Forty-six eyes with chronic open-angle glaucoma (COAG) and 24 eyes which had previously undergone trabeculectomy for COAG were studied and the postural response of the intraocular pressure compared with that of 70 normal eyes. In all three groups the greatest rise in intraocular pressure (IOP) occurred when the subject changed from the sitting to the lying position. In the control group this was never more than 2 mmHg in any subject. The rise was greater than 2 mmHg in 93% of the patients suffering from COAG who were treated medically and in 100% of the eyes of those on which trabeculectomy had been performed. The well recognised abnormal postural response of intraocular pressure in COAG appears both to be retained and to be unaffected in those eyes which have undergone trabeculectomy.